2012
DOI: 10.4236/jmmce.2012.119080
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sintered Ceramic Tiles Produced from Steel Slag

Abstract: Ceramic tiles were processed in this present work using clay mineral and steel slag. Steel slag in the range of 0 -100 wt% was added to kaolinite clay. The blended samples were hydraulic pressed into rectangular moulds, oven dried and sintered to 1200˚C. Linear shrinkage, apparent porosity, water absorption, bulk density, and modulus of rupture of sintered specimens were examined. Phases present in the sintered products were identified using X-ray Diffractometer (XRD), while the microstructural examination was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…It cannot be denied that CaO compound (larnite and gehlenite) from EAF slag could also contribute to the crystalline phases. However, it was reported that higher sintering temperature (1200-1500°C) is required to form anorthite and wollastonite from the CaO compound in the EAF slag (He et al, 2012;Chukwudi et al, 2012). Since lower sintering temperature (1150°C) was applied in this experiment, it can be deduced that formation of the crystalline phases due to SiO 2 and Al 2 O 3 is more dominant than CaO compound.…”
Section: Phase Analysismentioning
confidence: 72%
“…It cannot be denied that CaO compound (larnite and gehlenite) from EAF slag could also contribute to the crystalline phases. However, it was reported that higher sintering temperature (1200-1500°C) is required to form anorthite and wollastonite from the CaO compound in the EAF slag (He et al, 2012;Chukwudi et al, 2012). Since lower sintering temperature (1150°C) was applied in this experiment, it can be deduced that formation of the crystalline phases due to SiO 2 and Al 2 O 3 is more dominant than CaO compound.…”
Section: Phase Analysismentioning
confidence: 72%
“…Iron ore tailing, steel slag and blast furnace slag (BFS) are examples of solid industrial waste which has been converted into value added products in recent years [2,3]. BFS is a byproduct of steel production, discharged from blast furnaces in the steel smelting process, essentially consisting of SiO 2 , CaO, Al 2 O 3 , MgO, along with other compounds such as FeO, TiO 2 , and MnO 2 [4].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, China's crude steel production was 928 million tons; however, the recycling rate was about 30%. erefore, this problem has attracted much attention during the past years and has been explored in many fields [18,19]. In the field of steel and metallurgy, steel slag can be used in metal recovery [20] and to prepare compound desulfurase [21].…”
Section: Introductionmentioning
confidence: 99%